Archaeology in the lowland American tropics : current analytical methods and applications - Stahl, Peter W. (Cambridge ; New York : Cambridge University Press, 1995)
"Collection of 11 papers about analytical methods and their recent applications. Methods include survey techniques, community organization, landscapes, environmental stress, paleoethnobotany, plant microfossils, zooarchaeology, human osteology, stable isotope analysis, pottery analysis, and historical evidence. Regional coverage includes Puerto Rico, Panama, Ecuador, Colombia, Bolivia, and Peru"--Handbook of Latin American Studies, v. 57.
9. Interpreting dietary maize from bone stable isotopes in the American tropics: the state of the art / Lynette Norr -- 10. From potsherds to pots: a first step in constructing cultural context from tropical forest archaeology / J. Scott Raymond -- 11. Returning to Pueblo Viejo: history and archaeology of the Chachi (Ecuador) / Warren R. Deboer.
Includes bibliographical references (p. 263-304) and index.
Keywords: Lathrap, Donald Ward, -- 1927-; Indians of South America -- Antiquities; Archaeology -- Methodology; Tropics -- Antiquities; South America -- Antiquities